The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/jcm8091458
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training in Patients with Chronic Respiratory Diseases: Are Cardiovascular Comorbidities and Outcomes Taken into Account?—A Systematic Review

Abstract: Patients with chronic obstructive pulmonary disease (COPD), asthma and interstitial lung diseases (ILD) frequently suffer from cardiovascular comorbidities (CVC). Exercise training is a cornerstone intervention for the management of these conditions, however recommendations on tailoring programmes to patients suffering from respiratory diseases and CVC are scarce. This systematic review aimed to identify the eligibility criteria used to select patients with COPD, asthma or ILD and CVC to exercise programmes; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 219 publications
(436 reference statements)
0
8
0
Order By: Relevance
“…The exercise was known to treat many autoimmune and inflammatory diseases, such as chronic lung diseases and atherosclerosis because AE had immunomodulatory effects and modulated redox balance 8 10 . Previous researches demonstrated that LPS injection led to an excessive inflammatory response and oxidative stress injury and LPS injection generally accepted as somewhat modeling the septic condition 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The exercise was known to treat many autoimmune and inflammatory diseases, such as chronic lung diseases and atherosclerosis because AE had immunomodulatory effects and modulated redox balance 8 10 . Previous researches demonstrated that LPS injection led to an excessive inflammatory response and oxidative stress injury and LPS injection generally accepted as somewhat modeling the septic condition 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a precise patient’s stratification is the cornerstone of specific physiotherapy interventions tailored to patient’s characteristics ( 56 ). Accordingly, the present systematic review and meta-analysis includes acute critical patients with no previous chronic respiratory conditions that might have affected respiratory mechanics or the potential respiratory muscles response to training ( 57 59 ). Our findings emphasize the positive contribution of specific IMT strategies using a threshold load that deeply characterizes the rehabilitation strategies inducing specific results on lung function ( 34 , 37 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The Global Initiative for Chronic Obstructive Lung Disease (GOLD) suggests that patients with grade 3-4 COPD would benefit from nutritional support during lung rehabilitation. 10,[13][14][15] Purposeful adjustment of nutritional intake could improve prognosis and reduce acute episodes and the length of readmissions. 16 Studies have shown that high-calorie diets or the maintenance of obesity can improve lung function of some patients with COPD, whereas excessive ingestion result in the obesity will exacerbate hypoxia.…”
Section: Introductionmentioning
confidence: 99%